Method and experimental study of 2-D NMR logging - Liao, Guangzhi; Xiao, Lizhi; Xie, Ranhong (Diffusion Fundamentals, 2009)
Two-dimension (2D) NMR measurements have been performed to provide more information for qualitative identification and quantitative evaluation of the reservoir-fluids both in numerical simulation and in laboratory experiments. The data acquired with variable echo spacing and waiting time was inverted by multi-exponential inversion method. We use these 2D inversion results to identify fluid types and calculate fluid-saturation. We also detect the distribution of internal field gradients of core samples which contain paramagnetic minerals.